Hubungan Konsep Diri dan Kepuasan Kerja dengan Sikap Kerja Guru TK di Kecamatan Mandau Kabupaten Bengkalis - Kasmi Rahayu; Zulher Zulher; Yusuf Yusuf (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The purpose of this research is to determine the relationship between self-concept and teacher work attitudes, the relationship between job satisfaction and teacher work attitudes, and the relationship between self-concept and job satisfaction together with teacher work attitudes. This research was carried out at Pembina State Kindergarten, Al Kausar Kindergarten and Aisiyah 1 Kindergarten, Mandau District, Bengkalis Regency. The research method uses survey methods and area sampling techniques. This type of quantitative research uses a sample of 40 people. Data was collected using a questionnaire by giving respondents a set of written statements to answer which had been tested for validity and reliability. The data obtained were analyzed using product moment correlation (Pearson) so that there was a positive relationship between self-concept and teacher work attitudes of 32.3%, and there was a positive relationship between job satisfaction and teacher work attitudes of 36.1%, and there was a positive relationship between self-concept and job satisfaction together with teacher work attitudes is 40.1%. It is clear that the better the self-concept and the higher the job satisfaction, the higher the work attitudes of kindergarten teachers in Mandau District, Bengkalis Regency. Based on the research findings, it can be concluded that the work attitudes of kindergarten teachers in Mandau District, Bengkalis Regency are determined by self-concept and job satisfaction factors simultaneously.